BRAND AWARENESS INFLUENCES BEHAVIOR TEJA MEMBERS MEMBER CLUB (TMC) ON THE SELECTION OF MEDICAL SERVICES IN HOSPITALS - Rezkiah, Fahmy; Hariyanti, Tita; Rasyid, Harun Al (Universitas Brawijaya, Indonesia, 2017)
Marketing is an effort of the hospital to get and keep the customers. This study aimed to know the influence of brand (brand image and brand awareness), social factors and personal factors to the behavior of Teja Member Club (TMC) on choosing the health services in Teja Husada Hospital. This research categorized as explanatory research with cross sectional approach. This research involved 62 members of TMC. Questionnaires about brand image, brand awareness, social factors and personal factors as well as the behavior of members of TMC on choosing the health services in Teja Husada Hospital were used. The data analysis used linear regression test with White's Robust Standard Error. The results found all independent variables influence simultaneously to the behavior of members of TMC on choosing the health services in Teja Husada Hospital and brand awareness is the dominant variable. Partial test results indicate that only brand awareness that has an influence on the behavior of respondents on choosing the health services in Teja Husada Hospital.